2017
DOI: 10.1111/plb.12671
|View full text |Cite
|
Sign up to set email alerts
|

A role for fruit structure in seed survival and germination of Swartzia langsdorffii Raddi beyond dispersal

Abstract: Diaspore structure has been hypothesised to play a role in seed viability and/or germination of recalcitrant seeds, especially for Swartzia langsdorffii. Thus, this work aims to (i) investigate the in situ contribution of pericarp and aril on seed viability and germination, and (ii) identify morphoanatomical traits of S. langsdorffii diaspores that allow its desiccation-sensitive seeds to remain viable. The role of the pericarp and aril in seed survival and germination was investigated by placing the whole fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Various authors have reported different viability percentages in Magnolia species: 78 % for M. iltisiana (Saldaña-Acosta et al 2001), 100 % for M. dealbata (Corral-Aguirre & Sánchez-Velásquez 2006), 80 % for M. schiedeana (Vásquez-Morales & Sánchez-Velásquez 2011), 92 and 87.5 % for M. perezfarrerae and M. sharpii, respectively (Vásquez-Morales & Ramírez-Marcial 2019). Habitat characteristics, longevity during storage, seed moisture content, and the morpho-anatomical features of recalcitrant seeds explain this variability (Ibrahim & Roberts 1983, Vaz et al 2018. Our main conclusion in this experimental study on the effect of increased temperature and drought stress on the germination of Magnolia pugana seeds is that the interaction of simulated drought and temperature increases affected decreasing germination percentages and delaying the mean germination time.…”
Section: Discussionmentioning
confidence: 67%
“…Various authors have reported different viability percentages in Magnolia species: 78 % for M. iltisiana (Saldaña-Acosta et al 2001), 100 % for M. dealbata (Corral-Aguirre & Sánchez-Velásquez 2006), 80 % for M. schiedeana (Vásquez-Morales & Sánchez-Velásquez 2011), 92 and 87.5 % for M. perezfarrerae and M. sharpii, respectively (Vásquez-Morales & Ramírez-Marcial 2019). Habitat characteristics, longevity during storage, seed moisture content, and the morpho-anatomical features of recalcitrant seeds explain this variability (Ibrahim & Roberts 1983, Vaz et al 2018. Our main conclusion in this experimental study on the effect of increased temperature and drought stress on the germination of Magnolia pugana seeds is that the interaction of simulated drought and temperature increases affected decreasing germination percentages and delaying the mean germination time.…”
Section: Discussionmentioning
confidence: 67%
“…The arils of litchis and longans evolved from the funicle of the ovule after fertilization. So far, many studies have shown that, in addition to the rewards for seed dispersers [27,28], the arils have multiple roles, including protection of the seeds from water loss and regulation of seed germination time to enhance survival under unfavorable weather conditions [20,30]. Here, we suggest that, in litchi and longan fruits, arils evolved not just for providing means for seed dispersal like fleshy fruit but also for other physiological roles due to their water-rich [20] and sugar-rich features for the purpose of germination and seedling establishment.…”
Section: Discussionmentioning
confidence: 99%
“…Evrard [29] reported that the presence of the aril lowered the seed germination rate of Afzelia bipindensis, for the aril may contain growth inhibitors such as flavonoids, which are necessary to temporarily promote seed longevity. Our previous and other studies have reported that the pericarp and aril could help to retain seed moisture and favor viability maintenance of these seeds in the dry spells of the wet season [20,30]. In litchi and longan fruits, whether the sugar-rich arils and the "sugar receding" of arils can modulate the seed germination vigor during unpredictable dry weather is unknown.…”
Section: Introductionmentioning
confidence: 98%